1995
DOI: 10.1073/pnas.92.5.1322
|View full text |Cite
|
Sign up to set email alerts
|

Targeted overexpression of luteinizing hormone in transgenic mice leads to infertility, polycystic ovaries, and ovarian tumors.

Abstract: Hypersecretion of luteinizing hormone (LH) is implicated in infertility and miscarriages in women. A lack of animal models has limited progress in determining the mechanisms of LH toxicity. We (7)], it is difficult to devise protocols for chronic administration of exogenous LH that mimic endogenous pulse patterns of LH. To circumvent this limitation, we report a transgenic mouse model in which elevated hormone levels are maintained chronically, without requiring multiple injections,The publication costs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
192
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(212 citation statements)
references
References 28 publications
7
192
3
Order By: Relevance
“…Although there are some differences between ovarian steroidogenesis and ovarian tumor formation, many similarities exist between bLH-CTP overexpressing female mice and our mice, including the formation of pituitary and mammary gland tumors, obesity and infertility (Risma et al, 1995;Rulli et al, 2002;Kero et al, 2003;Mann et al, 2003;Mohammad et al, 2003). The ovarian tumor formation in bLHβ-CTP mice was found to be dependent on mouse strain (Keri et al, 2000), and we have not yet breed our mice to those strains susceptible to formation of ovarian tumors (Keri et al, 2000).…”
Section: Hcg Overexpressing Transgenic Micementioning
confidence: 89%
See 1 more Smart Citation
“…Although there are some differences between ovarian steroidogenesis and ovarian tumor formation, many similarities exist between bLH-CTP overexpressing female mice and our mice, including the formation of pituitary and mammary gland tumors, obesity and infertility (Risma et al, 1995;Rulli et al, 2002;Kero et al, 2003;Mann et al, 2003;Mohammad et al, 2003). The ovarian tumor formation in bLHβ-CTP mice was found to be dependent on mouse strain (Keri et al, 2000), and we have not yet breed our mice to those strains susceptible to formation of ovarian tumors (Keri et al, 2000).…”
Section: Hcg Overexpressing Transgenic Micementioning
confidence: 89%
“…The male mice were infertile without elevated bioactive LH/hCG and without obvious testicular phenotype, and the authors speculate that high circulating hCGβ-subunit could bind to the LH/hCG-R and antagonize the effect of normal circulating LH, thus interfering with spermatogenesis in a quantitative manner (Matzuk et al, 2003). In the other TG mouse model, which expresses a fusion protein of the bovine LHβ subunit and the hCGβ C-repminal peptide (bLHβ-CTP) under common α-subunit promoter, males did not show elevated LH/hCG-bioactivity and presented with no apparent phenotype (Risma et al, 1995).…”
Section: Hcg Overexpressing Transgenic Micementioning
confidence: 99%
“…Studies on experimental animals have also supported the gonadotropin theory. In inhibin-a-deficient mice, gonadotropins are essential for gonadal and adrenal tumorigenesis , and chronically elevated circulating levels of LH or human chorionic gonadotropin (hCG) can cause ovarian tumors in certain strains of mice (Risma et al, 1995;Rulli et al, 2002). Furthermore, in male rats, chronic treatment with LH produces Leydig cell hyperplasia (Neumann, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Even a mild diminution of LH clearance would be predicted to affect the pulsatility of circulating LH and to lead to an increased concentration of the hormone during the interpulse period. The most extreme form of such a disruption, the complete elimination of LH pulsatility and the continuous exposure of the ovary to elevated circulating levels of the hormone, has been modeled by overexpressing LH in transgenic mice (6). The phenotype seen in these animals includes ovarian cyst formation, ovarian tumorigenesis, and sterility, markedly different effects from those reported by Mi and associates.…”
Section: The Endocrine Phenotype Of M/g4sr -/+ Femalesmentioning
confidence: 79%
“…Structural analyses from Baenziger's group indicate that LH is modified by GalNAc-4-SO 4 , a specific and somewhat unusual glycan now known to bind the endothelial form of the Man/GalNAc-4-SO 4 receptor. They have suggested that binding of this receptor to the glycan-bearing hormone accounts for rapid clearance of LH, which is crucial to explain the pulsatile delivery of plasma LH (6). In their present article (1), this group has now explored the postulated role of the receptor in female reproduction.…”
mentioning
confidence: 97%